2002
DOI: 10.17221/5827-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the detection and quantification of rabies antibodies in canine sera

Abstract: 218Detection and quantification of rabies antibodies is intended in the first place for checking the immunity to rabies or effectiveness of rabies vaccines. Detection and quantification of virus neutralisation rabies antibodies in the serum is based on inhibition of rabies infection in vivo in animals or in vitro in cell cultures (Atanasiu, 1973;Bourhy and Sureau, 1991). Several suitable procedures have been recommended for determination of titres of virus neutralisation antibodies. e methods most frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Following seroconversion, protection from rabies virus challenge correlates with peak VNA titre and final titre prior to challenge for inactivated, DNA and modified-live vaccines, with increased susceptibility to challenge once titres drop to near negligible levels (VNA titres <0.1 IU/ml or mouse serum neutralizing antibody titres <1∶2 dilution) [31] – [35] , [37] – [41] . These studies used comparable antibody assays [42] , [43] and virus challenge doses. Titres measured repeatedly over 3–4 years initially peaked and then declined rapidly, followed by a more gradual decline [31] , [33] , [34] , [44] .…”
Section: Introductionmentioning
confidence: 99%
“…Following seroconversion, protection from rabies virus challenge correlates with peak VNA titre and final titre prior to challenge for inactivated, DNA and modified-live vaccines, with increased susceptibility to challenge once titres drop to near negligible levels (VNA titres <0.1 IU/ml or mouse serum neutralizing antibody titres <1∶2 dilution) [31] – [35] , [37] – [41] . These studies used comparable antibody assays [42] , [43] and virus challenge doses. Titres measured repeatedly over 3–4 years initially peaked and then declined rapidly, followed by a more gradual decline [31] , [33] , [34] , [44] .…”
Section: Introductionmentioning
confidence: 99%
“…The FAVN test is a modified method or an adjusted RFFIT, which belongs among the standard WHO methods for the determination of antibody titers. RFFIT requires the manual counting of the number of fluorescent foci in virus-infected cells [ 11 ], whereas FAVN is objective and suitable for large-scale samples, thereby enabling automated high-throughput detection. The conventional FAVN and RFFIT methods require a FITC-conjugated monoclonal antibody to identify positive or negative cells by the green fluorescence of FITC using fluorescence microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantification of the VNA levels against RABV is essential for the timely monitoring of immunization coverage in dog and cat populations and to evaluate the immunity effectiveness of RABV vaccines. According to the WHO, vaccinated animals are sufficiently protected from RABV when the levels of rabies VNA equal or exceed 0.5 IU/mL [ 11 ]. The principle of the detection and quantification of VNA titers is that the cells or animals are infected with viruses not inhibited by antibodies in vitro or in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…However, at least 3 injections are required to provide a sufficient virus neutralizing antibody (VNA) titer (at least 0.5 IU/ml), which is a reliable indicator that immune protection against rabies virus infection has been achieved [9,10]. In fact, the rabies neutralizing antibody titer is the most reliable indicator of immune protection [11]. Previous studies have shown that nearly one-third of dogs that received only one injection of a commercial rabies vaccine failed to produce a VNA titer of 0.5 IU/ml [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%